O nascimento da arte no espírito da guerra - Cavargere, Claudio Rebello de Oliveira (2022)
The present work aims to investigate the warlike powers of the conventionally called works of art. For this purpose, and taking the archaic Hellenic scenario as a starting point, we seek to investigate whether or not artistic potency can serve as a vital tonic, a pharmakon that at the same time amplifies, potentiates, fortifies, also diminishes, empties, the pulsating vitality of a body. In this sense, the work of art is questioned based on its material force, that is, as a condensed energy charge, a force or crystallized matter that enables or decays a form of life. Of an imminently tragic character, the work of art, conceived in this way, could only be an instrument of war, that is, a warrior effort to make life in the world possible